Green resilience: unlocking the nature's healing touch / Mia Emily Abdul Rahim and Emma Marini Abdul Rahim - Abdul Rahim, Mia Emily; Abdul Rahim, Emma Marini (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Ecopsychology, a field that explores the relationship between humans and nature and its impact on human health, has gained significant attention in recent years. The concept of nature-deficit disorder, introduced by Richard Louv in his book "Last Child in the Woods: Saving Our Children from Nature-Deficit Disorder", highlights the negative consequences of reduced exposure to nature especially in children. This theory is further supported by Chawla (2011), who emphasizes the importance of human restoration through the "Nature Principle" and the adverse effects of nature deficit disorder. Cervinka et al. (2011) also contribute to this concept by discussing the indicators of well-being and connectedness with nature, emphasizing the relevance of nature to human health. The following literature review supports the theory of ecopsychology, demonstrating the significant impact of nature on human health and wellbeing. The evidence presented underscores the importance of nature in promoting psychological restoration, wellbeing, and connectedness, emphasizing the need for further exploration of nature based interventions in promoting mental health.